Intellectual property and ethics - Bently, Lionel (Sweet & Maxwell LondonGB, 1998)
Covers a wide range of ethical theories and draws on a variety of issues in intellectual property law. Looks at the justification of intellectual property rights and the ethical underpinnings of familiar legal concepts. Examines the ethical dimensions of the encounter between intellectual property law and new geographies, spaces and cultures.